2005
DOI: 10.1161/01.hyp.0000170464.41776.98
|View full text |Cite
|
Sign up to set email alerts
|

Lys418Asn Polymorphism of the α2-Adrenoceptor Gene Relates to Serum Uric Acid Levels But Not to Insulin Sensitivity

Abstract: Abstract-Hyperuricemia is associated with cardiovascular risk. The present study examines the association between serum uric acid (UA) elevation and the ␣2-, ␤2-, and ␤3-adrenoceptor polymorphisms. In 219 nonobese, normotensive, normouricemic (serum UA Ͻ6.5 mg/dL at entry) men, serum UA, plasma norepinephrine (NE), the homeostasis model assessment of insulin resistance (HOMA-IR), body mass index, total body fat mass, the ␣2A(Lys418Asn)-, ␤2(Arg16Gly, Gln27Glu)-, and ␤3(Trp64Arg)-adrenoceptor polymorphisms were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Genotyping was performed by the TaqMan assay as previously described (16,19,21,22). Two polymorphisms in the β2-adrenergic receptors (arginine/glycine substitution, Arg16Gly; glutamine/glutamate substitution, Gln27Glu) of the β2-adrenoceptor genes (16,17) were evaluated.…”
Section: Genotypingmentioning
confidence: 99%
“…Genotyping was performed by the TaqMan assay as previously described (16,19,21,22). Two polymorphisms in the β2-adrenergic receptors (arginine/glycine substitution, Arg16Gly; glutamine/glutamate substitution, Gln27Glu) of the β2-adrenoceptor genes (16,17) were evaluated.…”
Section: Genotypingmentioning
confidence: 99%
“…The prevalence of obesity/overweight in Taiwan has been increasing alarmingly (Page et al, 2004;Ho and Tsai, 2007); therefore, an understanding of the fundamental mechanism of hyperuricemia becomes critical to prevent hyperuricemia in Han Chinese in Taiwan. Previous studies indicated that hyperuricemia was associated with a long list of candidate genes such as solute carrier family 2, member 9 (SLC2A9) (Rule et al, 2011), solute carrier family 22, member 12 (SLC22A12) ( Jang et al, 2008), and solute carrier family 17, member 3 (SLC17A3) (Polasek et al, 2010). Additional candidates include the genes encoding ATP-binding cassette, sub-family G, member 2 (ABCG2) (Yamagishi et al, 2010), klotho (KL) (Shimoyama et al, 2009), guanine nucleotide binding protein, beta polypeptide 3 (GNB3) (Suwazono et al, 2006), methylenetetrahydrofolate reductase (MTHFR) (Zuo et al, 2000), nitric oxide synthase 3 (NOS3) (Wang et al, 2007), adrenoceptor beta 2 (ADRB2) (Masuo et al, 2005), and adrenoceptor beta 3 (ADRB3) (Wang et al, 2002). However, considerable heterogeneity on the putative hyperuricemia loci was observed among different ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Increased activity of the sympathetic nervous system (SNS) may have an important role in the increased risk for cardiovascular and metabolic disease in patients with depressive and anxiety disorders (Glassman, 2008;Penninx et al, 2001;Eaker et al, 2005;Nicholson et al, 2006;Esler et al, 2006;Flaa et al, 2008a, b;Masuo et al, 2005Masuo et al, , 2010. Various studies reported increased sympathetic activity in depressed and anxious subjects compared with healthy controls, measured by different indices like spillover of norepinephrine (NE) and epinephrine (EPI), skin conductance responses, QT interval variability (QTvi), or the pre-ejection period (PEP) (Light et al, 1998;Esler et al, 1982;Guinjoan et al, 1995;Gold et al, 2005;Koschke et al, 2009;Barton et al, 2007).…”
Section: Introductionmentioning
confidence: 99%